DIAGNOSTIC PERFORMANCE OF ROSE BENGAL TEST, IGM/IGG ELISA, AND IS711-PCR FOR DETECTION OF HUMAN BRUCELLOSIS: A COMPARATIVE CROSS-SECTIONAL STUDY (European Science Methodical Journal, 2026)
Background: Human brucellosis is an important zoonotic disease with non-specific clinical manifestations that affect laboratory diagnosis. Reliable serological and molecular methods are needed to detect the disease. In this study, we assessed the performance of the Rose Bengal test (RBT), anti-Brucella IgM/IgG ELISA, and IS711-based PCR for the detection of human brucellosis. Methods: A comparative cross-sectional study, we investigated 101 clinically suspected patients. We collected blood samples and divided them into serological and molecular samples. Our sample was initially tested with Rose Bengal and IgM/IgG ELISA, and DNA extracted from EDTA whole blood samples was then subjected to conventional PCR targeting the Brucella melitensis IS711 insertion sequence, producing a 585 bp amplicon. Statistical analysis was performed with Chi-square test and ROC curve to assess diagnostic performance. Results: Rose Bengal test was the most positive (44.5%), followed by ELISA IgG (37.6%), ELISA IgM (28.7%), and PCR confirmed 23.8% of cases. The diagnostic methods had significant differences (p < 0.05). For PCR, AUC = 0.92 (ROC) and diagnosis was determined by sensitivity of 92% and specificity of 95%. ELISA IgM showed moderate success (AUC = 0.78), followed by ELISA IgG (AUC = 0.63), and the Rose Bengal test showed the lowest accuracy (AUC = 0.52). Conclusion: IS711-PCR was significantly more accurate for human brucellosis, while the Rose Bengal and ELISA methods are good for rapid screening. Diagnostic reliability can be improved by serological tests paired with PCR.